Marking the sparrow's fall : Wallace Stegner's American West - Stegner, Wallace, 1909-1993 (H. Holt, 1998)
Marking the Sparrow's Fall is Wallace Stegner's biggest collection and the first since his death in 1993. His son, Page, has selected fifteen essays that have never before been published in any book and placed them alongside Wallace Stegner's most powerful pieces in the book's three nonfiction parts: Home Ground (memory), Testimony (defense of the earth), and Inheritance (history). The fourth section of the book is devoted to a magnificent little-known novella, Genesis.